2022
DOI: 10.3389/fnagi.2022.943392
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and contextual factors modulating grammar learning at older ages

Abstract: Second language learning has been shown more difficult for older than younger adults, however, the research trying to identify the sources of difficulty and possible modulating factors is scarce. Extrinsic (learning condition and complexity) and intrinsic factors (executive control) have been related to L2-grammar learning in younger adults. In the present study, we aim to assess whether extrinsic and intrinsic factors are also modulating grammar learning in older adults. We compared the learning performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…It also improves emotional well-being by increasing self-confidence and encouraging a positive attitude. Previous research similarly found out that learning English among the third-age learners brought socio-cognitive benefits to their lives (Pfenninger & Polz, 2018), promoted mental health (Brouwer et al, 2020;Nijmeijer et al, 2021;Grossmann et al, 2021), developed linguistic skills (Słowik-Krogulec, 2020), self-actualization (Lee, 2020;Klimova, 2020), general well-being and quality of life (Kramkowska et al, 2019;Pikhart & Klimova, 2020), and positive effects on the brain (Gabryś-Barker, 2020; Nilsson et al, 2021;Rivera et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…It also improves emotional well-being by increasing self-confidence and encouraging a positive attitude. Previous research similarly found out that learning English among the third-age learners brought socio-cognitive benefits to their lives (Pfenninger & Polz, 2018), promoted mental health (Brouwer et al, 2020;Nijmeijer et al, 2021;Grossmann et al, 2021), developed linguistic skills (Słowik-Krogulec, 2020), self-actualization (Lee, 2020;Klimova, 2020), general well-being and quality of life (Kramkowska et al, 2019;Pikhart & Klimova, 2020), and positive effects on the brain (Gabryś-Barker, 2020; Nilsson et al, 2021;Rivera et al, 2022).…”
Section: Discussionmentioning
confidence: 94%